ANALYSIS OF THE QUALITY OF MARRIAGE REGISTRATION ADMINISTRATIVE SERVICES AT THE OFFICE OF RELIGIOUS AFFAIRS (KUA) IN TANETE RILAU DISTRICT, BARRU DISTRICT - Asriani Asriani; Masyitah Masyitah; Eka Nurul Asmi (Jurnal Scientia, 2023)
Eka Nurul Asmi Analysis of Quality Of Marriage Registration Administration Services at The Office of Religious Affairs Tanete Rilau District Barru District.This study aims to know the Analysis of The Quality of Marriage Registration Administration Services At the Office of Religious Affairs Tanete Rilau District Barru District, in use of research indicators: Tanggibles ( Direct evidence) , Realibility ( Reliability) , Responsiveness ( Responsiveness) , Assurance ( Guarantee) Emphaty ( Empathy) and To know the factors that affect the Analysis of The Quality of Marriage Registration Administration Services At the Office of Religious Affairs Tanete Rilau District Barru district used research indicators: Organizational structure factors, Public Apparatus Factors, Public Service System Factors Types of research used qualitative descriptive.The results showed the Quality of Marriage Registration Administration Services in the Office of Religious Affairs Tanete Rilau District Barru district in the category is quite high, factors that affect the Quality of Marriage Registration Services In the Office of Religious Affairs Kec. Tanete Rilau Kab, barru are: Organizational Structure, Ability of Public Service Apparatus, And Public Service System.